Impact of AI in Education and Social Development through Individual Empowerment - Muhammad Guruh Nuary; Loso Judijanto; Elly Siti Nurliyah; Muriyanto Muriyanto; Samar A. El-Farra (Journal of Artificial Intelligence and Development, 2022)
This research investigates the transformative impact of Artificial Intelligence (AI) on education and social development through individual empowerment. Leveraging a systematic literature review approach, the study examines the multifaceted implications of AI integration in educational and social contexts, with a specific focus on its role in personalized learning, access to education, and socio-economic empowerment. The findings underscore the significant advancements facilitated by AI technologies in enhancing educational outcomes, increasing access to quality education for marginalized populations, and promoting socio-economic mobility. However, the research also highlights the importance of addressing ethical considerations, algorithmic bias, and equitable access to ensure that the benefits of AI are equitably distributed across diverse populations. Moving forward, future research directions include interdisciplinary studies, longitudinal analyses, comparative research across different socio-cultural contexts, and participatory approaches to inform the development of inclusive and sustainable AI solutions that empower individuals and promote social justice.